2012
DOI: 10.1103/physrevlett.108.195505
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Structure and Structural Relaxation inZr50Cu45Al5Bulk Metallic Glass

Abstract: Hybrid reverse Monte Carlo simulations of the structure of Zr50Cu45Al5 bulk metallic glass incorporating medium-range structure from fluctuation electron microscopy data and short-range structure from an embedded atom potential produce structures with significant fractions of icosahedral- and crystal-like atomic clusters. Similar clusters group together into nanometer-scale regions, and relaxation transforms crystal-like clusters into icosahedral clusters. A model refined against only the potential does not ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
88
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(101 citation statements)
references
References 42 publications
10
88
0
Order By: Relevance
“…Among them, the fraction of the Z16 cluster showed a remarkable growth (2.75 times higher) [22]. On the other hand, the fraction of crystal-like atoms has a little decreased and it indicates that the crystal-like clusters would transform into the icosahedral ones by annealing, which is consistent with a recent experimental observation in Zr50Cu45Al5 bulk metallic glasses [11]. In the same relaxed phase, 96.7% of the icosahedron-like clusters are the (smaller) B atom-centered, while 99.7% of the Z16 cluster-like clusters are the (larger) A atom-centered.…”
Section: Low Distortion 5-rings and Alloy Compositions Of Good Glass-supporting
confidence: 81%
See 1 more Smart Citation
“…Among them, the fraction of the Z16 cluster showed a remarkable growth (2.75 times higher) [22]. On the other hand, the fraction of crystal-like atoms has a little decreased and it indicates that the crystal-like clusters would transform into the icosahedral ones by annealing, which is consistent with a recent experimental observation in Zr50Cu45Al5 bulk metallic glasses [11]. In the same relaxed phase, 96.7% of the icosahedron-like clusters are the (smaller) B atom-centered, while 99.7% of the Z16 cluster-like clusters are the (larger) A atom-centered.…”
Section: Low Distortion 5-rings and Alloy Compositions Of Good Glass-supporting
confidence: 81%
“…The early works of computer simulation have shown that the icosahedral order would exist in both liquid and glassy phases [3,4]. After the discovery of good metallic glass-formers [5,6], experimental observations [7][8][9][10][11][12] has reported that the icosahedral short-range order does exist in metallic glasses and that some medium-range order may also exist beyond the icosahedral short-range order. However, it was little known how the icosahedral short-range order is arranged and extended to form a medium-range order in glassy phases.…”
Section: Introductionmentioning
confidence: 99%
“…Hwang et al 38 observed nanoscale crystal-like superclusters in the Zr 50 Cu 45 Al 5 MGs, in their model based on reverse Monte Carlo modeling constrained at short range by an empirical interatomic potential and at medium range by fluctuation electron microscopy data (as shown in Fig. 8a).…”
Section: -100mentioning
confidence: 99%
“…Examples include a structural signature of dynamical slowdown as well as the liquid fragility in metallic glass-forming liquids, [26][27][28][29][30][31][32] anomalous thermal contraction of metallic melts in the nearest-neighbor shell, [33][34][35] possible crystallike order in MGs/liquids, [36][37][38][39] a fractal structure model of MGs, [40][41][42] advanced algorithms (such as machine learning methods) to efficiently characterize the structural basis of flow defects and dynamical slowdown in amorphous materials, 43,44 and a new structure parameter that incorporates dynamic (atomic vibration) information beyond the description of static structure/ configuration. [45][46][47][48][49] Computational research has played a key role in formulating these ideas.…”
Section: Introductionmentioning
confidence: 99%
“…In this state, although almost all the molecules are in locally crystalline environments, there is no long-range crystalline order, and so the S(k) is liquid-like. It is a fascinating open question as to whether this medium-rangecrystalline/paracrystalline/nanocrystalline order is also present in any of: amorphous silicon, [1][2][3] two-line ferrihydrite, 4-6 metallic glasses, 35 polymers, 36 ACC, 7-16 ACP 17 and ACS. [18][19][20] Whether or not these materials have this ordering has consequences.…”
mentioning
confidence: 99%